Case studies in public health ethics - Coughlin, Steven S. (Steven Scott), 1957- (American Public Health Association, 2009)
"This new edition covers issues of privacy and confidentiality protection, informed consent in public health research, the ethics of randomized trials, vulnerable populations, genetic discrimination, AIDS prevention and treatment, health care reform, scientific misconduct, conflicts of interest, intellectual property, and more."--Publisher's description.